Simulating of RF energy harvesting micro-strip patch antenna over 2.45 GHZ - S.Bilal, Bilal; M. Marhoon, Hamzah; Ahmed A. Naser, Ahmed (International Journal of Engineering and Technology, 2019)
This paper dealing with simulation a proper antenna design for RF energy harvesting. The energy harvesting technologies are rising gradually in the recent years because of limitation by energy storage and wired power supply. In the last energy decades’ energy emitted from external sources such as solar power, wind energy, and RF energy used in the features purposes to provides unlimited energy for the lifespan of electronic appliances, the energy harvesting are never-ending sources because the environment around us is filled daily with different radio signals from ground stations or through mobile towers. This paper focuses on RF energy harvesting over 2.45 GHz that’s which emitting from the Wi-Fi band. The receiving antenna picking up the radio signal that in the RF range (2.45 GHz) from the free space then converts it from a radiated electromagnetic wave into an alternating signal and via rectifier converted later into DC voltage, can be store the voltage inside battery or may be feeding the load directly, the position of antenna is most important, in other words the field strength is grater in the vicinity of the earth station than the areas away from the station. In this paper the semiconductor Schottky diode model SMS 7630-005LF choose because low forward voltage between (0.15-0.45) V and a very fast switching action.